Perception of Foreign Students Learning Turkish on Theır Willingness to Communicate in Turkısh - Ekinci, Muzaffer; Şahin, Tuğrul Gökmen; Bayrak, Özcan (My University, 2022)
The study, which was conducted in order to determine the willingness of foreign students learning Turkish as a second language to communicate in Turkish, was carried out with the participation of Afghan students studying at the Fırat University at undergraduate and graduate levels. The main purpose of this study is to determine the willingness of students who learn Turkish as a second language to communicate in Turkish, and to offer suggestions to increase the language teaching quality of those who learn Turkish as a second language, based on these findings. In the study, the phenomenology design from the qualitative research method was used. According to the findings of the study; although students generally describe themselves as inadequate in communicating in Turkish, it has been determined that they have a high willingness to communicate in Turkish, as they have individually assimilated Turkish and Turkish culture, and they do various activities while learning Turkish. According to the research findings, some suggestions were made to the researchers in order to illuminate the willingness of foreign students to communicate in Turkish in all aspects.
Keywords: Eğitim; Eğitim Araştırmaları; Kültürel Çalışmalar; Beşeri Bilimler; Antropoloji; Dil ve Dil Bilim